The Fiduciary Duties of Joint Venture Parties – When do They Arise and What Do They Comprise? - Knowler, Jane; Rickett, Charles (Victoria University of Wellington Law Review, 2011)
Joint Ventures are often used by parties in commercial enterprises where parties seek to achieve a common goal. One issue which is increasingly contentious is the extent to which, if any, joint venture parties owe each other fiduciary obligations. This paper refutes, as a dangerous heresy, the idea that joint venture relationships are discrete legal relationships that are inherently fiduciary in nature. The majority of self-styled "joint ventures" are, invariably, nothing more in legal terms than contracts. If parties are going to be bound by fiduciary duties, over and above the contractual duties they owe each other, this will only be so by virtue of the particular arrangement they have entered into which, on a thorough examination of the facts, is found to require each party to give unstinting loyalty to the other. Recent Australian case law bears this out.